2006
DOI: 10.1089/jam.2006.19.372
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for the Selection of an Aerosol Delivery System for Gene Delivery

Abstract: Genetic therapeutics show great promise toward the treatment of illnesses associated with the lungs; however, current methods of delivery such as jet and ultrasonic nebulization decrease the activity and effectiveness of these treatments. Extremely low transfection rates exhibited by non-complexed plasmid DNA in these nebulizers have been primarily attributed to poor translocation and loss of molecular integrity as a consequence of shear-induced degradation. Current research focusing on methods to increase tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 77 publications
1
18
0
Order By: Relevance
“…Compared to standard ultrasonic nebulization at 20–80 kHz, where cavitation is prevalent and large molecules like pDNA in solution actually serve as cavitation bubble nucleation sites [10] and cause wholesale destruction of such molecules, the damage caused by SAW nebulization is minor. For 5 kbp plasmids, the percentage of fragmented pDNA after nebulization is lower with SAW (<20%) than with conventional (>35%) or vibrating mesh nebulizers (>40%) [39]. Hence, the SAW nebulization approach has several key advantages over the current generation of ultrasonic medical nebulizers for the delivery of large molecules [19].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to standard ultrasonic nebulization at 20–80 kHz, where cavitation is prevalent and large molecules like pDNA in solution actually serve as cavitation bubble nucleation sites [10] and cause wholesale destruction of such molecules, the damage caused by SAW nebulization is minor. For 5 kbp plasmids, the percentage of fragmented pDNA after nebulization is lower with SAW (<20%) than with conventional (>35%) or vibrating mesh nebulizers (>40%) [39]. Hence, the SAW nebulization approach has several key advantages over the current generation of ultrasonic medical nebulizers for the delivery of large molecules [19].…”
Section: Discussionmentioning
confidence: 99%
“…Among these technologies, lyophilization has been the preferred approach to remove water due to the general perception that uncomplexed plasmids as well as oligonucleotides may undergo shear-induced damage [129][130][131][132] during the process of spray drying. However, recent studies on the mechanisms of nucleic acid shearinduced damage have concluded that smaller plasmids (~ 5 kb) are not as sensitive to shear stress as larger plasmids (~ 9.8 and 37 kb) [133,134] which is consistent with previous findings by Levy and collaborators where the level of damage during shear stress was found to be dependent essentially on plasmid size and ionic strength [135]. These findings are important when considering the practical challenges of producing large amounts of plasmid DNA for therapeutic use in humans, for both clinical trials, and, in the end, full-scale production.…”
Section: Preservation Of Dnamentioning
confidence: 99%
“…For instance, because of its viscosity, the concentration of DNA that can be readily nebulized is less than 5 mg/ml. Nebulization of solute and adhesion of DNA to plastic surfaces results in less than 10% of the DNA in a nebulizer cup's being emitted from the device [153,154].…”
Section: Aerosolization Of Biologicsmentioning
confidence: 99%